Water quality and residents' health: a survey by the self-assessed health method - Yan, Jing; Cui, Shuai (Frontiers in Public Health, 2025)
IntroductionWater is the source of life. The insufficient water resources and deteriorating water quality pose significant challenges to public health. This study investigates the impact of water quality on residents' self-assessed health rating using data from the 2016 China Genuine Progress indicator Survey. The analysis focuses on household cooking water sources (river/lake, well, tap, mineral/purified/filtered) and water pollution exposure in living or working environments.MethodsAn ordered probit (oprobit) model was employed to analyze the relationship between water quality and residents' self-assessed health ratings, controlling for accessibility of medical services, individual lifestyles, and socio-demographic characteristics. The study also conducted heterogeneity analysis based on socioeconomic status and robustness checks using alternative dependent variables and estimation methods.ResultsResults indicate that transitioning from river/lake water to safer sources-well, tap, and mineral/purified/filtered water-increases the probability of residents reporting self-assessed health ratings as “very good” by 7.9%, 10.4%, and 12.9%, while reducing the likelihood of “very bad or not very good” ratings by 7.2%, 9.4%, and 11.7%, respectively. Conversely, exposure to water pollution decreases the probability of “very good” health ratings by 2.4% and increases “very bad or not very good” ratings by 2.1%. The impact of cooking water quality on residents' health is more significant for lower socioeconomic status groups, while water pollution exposure affects higher socioeconomic status groups more. Robustness checks using hospitalization days as an alternative dependent variable and replacing oprobit with ologit/OLS models confirm these findings.DiscussionThe study underscores the critical role of safe water access and ecological protection in enhancing public health. Policy recommendations include using and managing water resources strictly for holistic water security, maximizing the potential of China's revised Environmental Protection Laws, establishing a cross-agency coordination mechanism to tackle pollution sources, and improving medical services and fitness facilities to advance the “Healthy China” initiative.